Y-2=x-(-2)

Simple and best practice solution for Y-2=x-(-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-2=x-(-2) equation:



-2=Y-(-2)
We move all terms to the left:
-2-(Y-(-2))=0
We calculate terms in parentheses: -(Y-(-2)), so:
Y-(-2)
We add all the numbers together, and all the variables
Y+2
Back to the equation:
-(Y+2)
We get rid of parentheses
-Y-2-2=0
We add all the numbers together, and all the variables
-1Y-4=0
We move all terms containing Y to the left, all other terms to the right
-Y=4
Y=4/-1
Y=-4

See similar equations:

| h+7h-5=8h-5 | | 1-5y=5+4y | | -2x1=3/4x+9 | | 294-v=165 | | 2x+32=3x–2 | | 21x+6=84 | | 7x-28=-2(5-8x) | | 20+1x=x+44 | | 12=2/3l | | 1+5y=5+4y | | 10(x-3)=x+15 | | 3(4c-2)=15c | | 8x-1=8x-4 | | 5(3x–6)=3(3x–8)+6x | | -5-4x=5x+4 | | x/4=2=6 | | -4w=-9–3w | | w-17=-11+16/w | | 13k−7k=6 | | 41.9=(-22)z | | 24+(9-2x)²=(4x-1)(5+x) | | 5y+32=14y-2 | | v−3=1 | | Y-(-10)=-(x-2) | | 5x3x=-24 | | 15x+1/5=7/15 | | 3x3x=6 | | (-8x-6+8)+(-6x-6+20)=112 | | 4x-2=4(x-2)+6 | | 2.5x-3+2.5x-3=2.5x-3+2.5-3 | | c+5=c+2 | | 18x-104=11x-69 |

Equations solver categories